4(-3+x)=6-2x

Simple and best practice solution for 4(-3+x)=6-2x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(-3+x)=6-2x equation:


Simplifying
4(-3 + x) = 6 + -2x
(-3 * 4 + x * 4) = 6 + -2x
(-12 + 4x) = 6 + -2x

Solving
-12 + 4x = 6 + -2x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '2x' to each side of the equation.
-12 + 4x + 2x = 6 + -2x + 2x

Combine like terms: 4x + 2x = 6x
-12 + 6x = 6 + -2x + 2x

Combine like terms: -2x + 2x = 0
-12 + 6x = 6 + 0
-12 + 6x = 6

Add '12' to each side of the equation.
-12 + 12 + 6x = 6 + 12

Combine like terms: -12 + 12 = 0
0 + 6x = 6 + 12
6x = 6 + 12

Combine like terms: 6 + 12 = 18
6x = 18

Divide each side by '6'.
x = 3

Simplifying
x = 3

See similar equations:

| 7a^2=32a-16 | | 5+5x-4x= | | 3h-12=33 | | 2x+11=59-8x | | 8r^2-34-9=0 | | 2a-7a=9-6a | | 4(4c-1)-4=13c+7 | | 31+5y-9=17y-14-3y | | x/13=-8 | | 8x-8=9x+8 | | -53+2i=-I+73 | | 4m+t= | | 4m+10=2m-6 | | 6-3x=14-7x | | -5(x-3)+2x=6 | | 14(2f)=7(f-2) | | 9y-(11)-(5y)=-25 | | -53-2i=-I+73 | | y/11=17 | | 6x+4=70 | | 2.4(3.1x+4.9)=75.9+0.87 | | m(m-3)=54 | | 5m-7= | | -4-(1-5)-4x-4= | | x/8=-6 | | 7x+17=3x+1 | | x/8=-7 | | 9y-11-5y=-25 | | 10x^2-2x-6=0 | | -6s+-15=15 | | 3=.33-2b | | 3k^2=-12-20k |

Equations solver categories